2014
DOI: 10.3748/wjg.v20.i32.11273
|View full text |Cite
|
Sign up to set email alerts
|

Enteric glial cells and their role in the intestinal epithelial barrier

Abstract: The intestinal epithelium constitutes a physical and functional barrier between the external environment and the host organism. It is formed by a continuous monolayer of intestinal epithelial cells maintained together by intercellular junctional complex, limiting access of pathogens, toxins and xenobiotics to host tissues. Once this barrier integrity is disrupted, inflammatory disorders and tissue injury are initiated and perpetuated. Beneath the intestinal epithelial cells lies a population of astrocyte-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 87 publications
3
99
0
Order By: Relevance
“…This would be indicating that ATX/LPA could exert a necessary effect during the first month of life. Recent studies have shown that LPA has stimulatory effects on fluid absorption in the intestine [18] . On the other hand, it has been suggested that ATX/LPA signaling could negatively influence adipose tissue development [19] .…”
Section: Discussionmentioning
confidence: 99%
“…This would be indicating that ATX/LPA could exert a necessary effect during the first month of life. Recent studies have shown that LPA has stimulatory effects on fluid absorption in the intestine [18] . On the other hand, it has been suggested that ATX/LPA signaling could negatively influence adipose tissue development [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Other factors contributing to homeostasis and maintenance of the permeability of the gut mucosa include the secretion of mucous and immunoglobulin cells, while pro-inflammatory cytokines secreted by inflammatory cells cause barrier disruption [97]. Inflammatory processes are known to facilitate destruction of the enteric glial cells which then leads to the breakdown of the epithelial lining [98]. More recently both preclinical and clinical studies have demonstrated an important role of the gut microbiota in maintaining the integrity of the intestinal epithelium.…”
Section: Candidate Mechanisms Underlying Gut Microbiota Induced Obesitymentioning
confidence: 99%
“…As the intestinal mucosal barrier serves as the interface between vastly diverse external and internal environments, the maintenance of homeostasis is critical to its ability to respond to noxious or pathogenic stimuli. Intestinal epithelial cells, immune cells of the lamina propria, and enteric glial cells (EGCs) regulate mucosal barrier homeostasis though complex and dynamic interactions 16,17 .…”
Section: Introductionmentioning
confidence: 99%